2012
DOI: 10.3950/jibiinkoka.115.22
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery Complications a Prospective Multicenter Study

Abstract: While care should be taken to avoid them, complications should be identified and treated in a timely and accurate manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…AEA injury was reported during ESS, indicating that it is a difficult task for surgeons to identify the AEA course. 26,27 AEA injury may result in major negative sequelae including sever epistaxis, retroorbital hematoma, blindness, cerebrospinal fluid leak, and/or intracranial bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…AEA injury was reported during ESS, indicating that it is a difficult task for surgeons to identify the AEA course. 26,27 AEA injury may result in major negative sequelae including sever epistaxis, retroorbital hematoma, blindness, cerebrospinal fluid leak, and/or intracranial bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…During endoscopic sinus surgery (ESS) which is essential for the treatment of chronic rhinosinusitis and removal of the sinonasal pathologies, accidental LP injury can be incurred. 4 , 5 Precise knowledge of LP localization according to inferior nasal turbinate (INT) attachment to the lateral nasal wall is essential to avoid orbital penetration. 4 As a consequence of LP penetration, periorbital ecchymosis or emphysema, venous orbital hematoma, medial rectus injury, and blindness can occur.…”
Section: Introductionmentioning
confidence: 99%
“…During Endoscopic Sinus Surgery (ESS) that is important for the treatment of chronic rhinosinusitis and removal of sinonasal pathology, accidental LP injuries can occur (3,4). Shigeta et al, reported the prevalence of LP injuries in their prospective study was 5.8% (1,5). Recognizing CT images from normal LP anatomy allows assessment on the targets of ESS and reconstructive surgery, including careful planning, the use of additional surgical approaches, efficient clearance of ethmoid air cells on LP, avoiding injury, and obtaining the exact dimensions of the implant (6).…”
Section: Introductionmentioning
confidence: 99%